2018
DOI: 10.1021/acs.chemmater.8b04173
|View full text |Cite
|
Sign up to set email alerts
|

Molecules under Pressure: The Case of [n]Cycloparaphenylenes

Abstract: High pressures in the 0-10 GPa range cause molecules to deform in unusual ways. A series of precisely defined carbon nanohoops consisting of n para-linked phenyl groups, [n]cycloparaphenylenes ([n]CPPs, n=7, 8, 9, 10, and 12) were studied in this pressure range using Raman spectroscopy and Density Functional Theory (DFT), and compared with more rigid smaller 5-and [6]CPPs and with the longer carbon nanotubes. The presented analysis sheds light on the different responses to pressure depending on the nanohoop si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 62 publications
3
11
0
Order By: Relevance
“…As in the compression of phase II of benzene [45], and in line with former results, the GA 1g mode of [6]LPP linearly upshifts [16,50]. The pressure at which the [n]CPPs change the slope and, thus, the cycle, becomes oval is higher the more strained and rigid the cycle is, in agreement with the change in slope at around 5 GPa in [6]CPP and below 1 GPa in [12]CPP [40]. In the case of the non-conjugated cycloparaphenylene H 4 [6]CPP, the C-C stretching mode from the aromatic units of H 4 [6]CPP linearly upshift to approximately 8 GPa, where there is a change in slope.…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…As in the compression of phase II of benzene [45], and in line with former results, the GA 1g mode of [6]LPP linearly upshifts [16,50]. The pressure at which the [n]CPPs change the slope and, thus, the cycle, becomes oval is higher the more strained and rigid the cycle is, in agreement with the change in slope at around 5 GPa in [6]CPP and below 1 GPa in [12]CPP [40]. In the case of the non-conjugated cycloparaphenylene H 4 [6]CPP, the C-C stretching mode from the aromatic units of H 4 [6]CPP linearly upshift to approximately 8 GPa, where there is a change in slope.…”
Section: Resultssupporting
confidence: 77%
“…It has been reported that compression of [12]CPP induces the deformation of the cycle towards a more oval configuration, creating shorter and longer diameters [7,40]. The onset of ovalisation is below 1 GPa [40]; however, the FTIR spectra presented in Figure 5c show that compression within the oval regime does not seem to affect the sp 2 framework as the C-H stretching modes broaden and upshift while maintaining their band shapes. After pressure is released, the spectrum is identical to that of the pristine sample.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations